PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN CV. ANGKUTAN TERANG MANDIRI (ATM) PALEMBANG - Dian Putri Permata Sari; Liliana Liliana (JURNAL KOMPETITIF, 2022)
The purpose of this study was to determine the effect of the work environment (X1), motivation (X2) and job satisfaction (X3) on employee productivity (Y) at CV Angkutan Mandiri (ATM) Palembang. The analytical tool used with SPSS, the data source used is primary data and secondary data with respondents as many as 75 people on CV employees. Bright Independent Transport (ATM) Palembang. Based on the results of the analysis of this study, it can be concluded that there is a simultaneous significant effect on employee productivity as indicated by a significance value of 0.000 <0.05. While partially the work environment variable has no effect on employee productivity as shown by the significant value of the t test (0.542 > 0.05). The motivation variable partially has no effect on employee productivity with the results of a significant value of the t test (0.365 > 0.05). While the job satisfaction variable partially has a significant effect on employee productivity with the results of a significant value of the t test (0.000 <0.05).Keywords: Work;Environment; Motivation; Job Satisfaction, and Employee Productivity.